2011
DOI: 10.1007/s00464-011-1778-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic fixation of the rectum for rectal prolapse: a feasibility and survival experimental study

Abstract: Endoscopic fixation of the mobilized rectum is feasible and safe in this model and in the future may provide an effective alternative to current treatment options for rectal prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[3][4][5] Natural orifice transanal surgery for rectal prolapse although feasible has largely remained experimental. [6][7][8] We have previously described a novel intraluminal technique for fixation of prolapsed rectum posteriorly to the sacral promontory and ventrally to abdominal wall. 9 This pilot study determined the feasibility of the procedure but was limited in being blind, hence potentially morbid, with suboptimal outcomes.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Natural orifice transanal surgery for rectal prolapse although feasible has largely remained experimental. [6][7][8] We have previously described a novel intraluminal technique for fixation of prolapsed rectum posteriorly to the sacral promontory and ventrally to abdominal wall. 9 This pilot study determined the feasibility of the procedure but was limited in being blind, hence potentially morbid, with suboptimal outcomes.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“…The fixation of the rectum to the anterior abdominal wall has been long described, but endoluminal techniques for ventral rectal fixation largely remain experimental. 6–8 Submucosal interventional endoscopy is a new minimally invasive endoluminal management option for difficult polypoidal lesions, carcinoma in situ, and now achalasia cardia (peroral endoscopic myotomy procedure). 19–21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milsom et al [12] proposed an endoluminal full thickness rectopexy to the anterior abdominal wall, similar to the technique used for percutaneous gastrostomy tube placement (PEG). The authors used a prototype, identified as the Brace Bar wire, in eight live swine and reported adequate fibrosis of the rectum to the abdominal wall without any immediate infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used a prototype, identified as the Brace Bar wire, in eight live swine and reported adequate fibrosis of the rectum to the abdominal wall without any immediate infectious complications. In addition, initial rectopexy security was superior to both ProTack (Covidien, Mansfield, MA) and TI•CRON suture (Covidien, Mansfield, MA) [12,13]. Follow-up for the Brace Bar wire, however, was limited only to 14 days, so the probability of late colocutaneous fistula development is still unknown.…”
Section: Discussionmentioning
confidence: 99%